2000
DOI: 10.1046/j.1365-2427.2000.00619.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of springtime water temperature on the time of emergence and size of Pteronarcys californica in the Henry's Fork catchment, Idaho, U.S.A.

Abstract: 1. The emergence time of Pteronarcys californica in streams in the Henry's Fork catchment, Idaho, U.S.A. was negatively correlated with mean April water temperature. Emergence was in mid‐ to late May at sites influenced by groundwater, where April water temperature averaged 7.9 °C. Adults emerged in mid‐June in streams receiving run‐off from snowmelt (mean April water temperature 5.4 °C). Intermediate emergence times were observed in a regulated section of river where water temperature was influenced, on one b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
31
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 18 publications
3
31
0
1
Order By: Relevance
“…The decline in size of R. vibox and I. montana over the season is a common pattern (Huryn 1996;Sweeney et al 1995;Peckarsky et al 2001) and suggests that warm summer temperatures may cause slower growth. As seen in this study, warm temperatures in spring do generally lead to earlier emergence (Hogg and Williams 1996;Gregory et al 2000). However, the smaller size at emergence in fishless streams is unlikely to be an effect of spring temperatures, as fishless streams did not warm more quickly than those with fish.…”
Section: Discussionsupporting
confidence: 58%
“…The decline in size of R. vibox and I. montana over the season is a common pattern (Huryn 1996;Sweeney et al 1995;Peckarsky et al 2001) and suggests that warm summer temperatures may cause slower growth. As seen in this study, warm temperatures in spring do generally lead to earlier emergence (Hogg and Williams 1996;Gregory et al 2000). However, the smaller size at emergence in fishless streams is unlikely to be an effect of spring temperatures, as fishless streams did not warm more quickly than those with fish.…”
Section: Discussionsupporting
confidence: 58%
“…Gregory et al (2000) found that April temperature was the best predictor for emergence of a Californian mayfly. Degree-day accumulation for egg incubation has been studied for several Australian mayfly species (Suter and Bishop, 1990;Brittain and Campbell, 1991;Brittain, 1995).…”
Section: Discussionmentioning
confidence: 96%
“…The larval growth of Nemouridae, Capniidae and Perlodidae in the Scandinavian stoneflies was largely positively influenced by water temperature (Brittain 1983). Water temperature affects the growth rate and emergence of stoneflies (Gregory et al 2000). Size of mature individuals depends on duration of larval development and growth rate, both of which are strongly influenced by temperature (Sweeney 1984;Perry et al 1987;Gregory et al 2000;Briers et al 2004;Krno, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Water temperature affects the growth rate and emergence of stoneflies (Gregory et al 2000). Size of mature individuals depends on duration of larval development and growth rate, both of which are strongly influenced by temperature (Sweeney 1984;Perry et al 1987;Gregory et al 2000;Briers et al 2004;Krno, 2006). Stonefly larval growth depended exponentially on water temperature (Elliot 1984(Elliot , 1987.…”
Section: Discussionmentioning
confidence: 99%